Improving health care management at the top : how balanced boardrooms can lead to organizational success - Roberts, Sharon. (Health care management collection., 2016)
In this book we explore the influence of gender on organizational performance in the health care sector. The authors argue that gender diversity of boards improves health care organizational performance when compared to homogeneous boards. The theoretical framework used was developed from conducting literature reviews of scholarly academic journal articles on gender, boards, and organizational performance as well as performing an in-depth study of the performance of health care organizations in Ontario, Canada. Research results suggest that effective boards and their composition were dependent on their female-to-male ratio to realize administrative efficiencies. Publicly funded, nonprofit, 126 acute care hospitals located in Ontario, Canada, were chosen as the health care sector for this research. Limitations of this study are in the complexity of the health care industry, competing internal and external priorities, and funding constraints. Nevertheless, this book is original work and relevant for use by boards to examine the complementary mix of gender as a predictor of organizational performance.